Geodetic Strain of the Baribis Fault Zone in West Java, Indonesia. Issue 1 (1st November 2022) - Susilo, S; Meilano, I; Wibowo, S T; Syetiawan, A; Gaol, Y A L; Ramdani, D; Julzarika, A
Abstract: The Baribis Fault's status, which is located in the northern part of Java, as an active or inactive fault is a matter of considerable debate. In this study, we investigate the strain rate of the Baribis fault zone's segment in northeastern West Java, Indonesia, as revealed by a dense network of GPS stations. We analyzed 17 surveyed GPS stations combined with continuous GPS sites over West Java from 2017 to 2021, then we estimate the GPS velocities fields. We calculated the strain rate and estimated it from the GPS velocities. In general, the Baribis fault zone experiences a significant strain rate (> 50 nano-strain/yr) with the compressional dilatation strain associated with the ongoing deformation in that area. The dilatation strain suggest that the northeastern Baribis fault in the West Java is an active thrust fault system. This information is essential to supporting a disaster mitigation program.